(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Cloud computing is used to provide scalable services which are easily used over the internet as per the requirement. A major feature of the cloud services is that users data are remotely processed in unknown machines that users do not know or users are not operating these machines. While using these services provided by cloud computing, users fear of losing their own data. The content of data can be financial, health, personal. To resolve this problem, we use information accountability in decentralized format to keep track of the usage of the users data over the cloud. It is object oriented approach that enables enclosing our logging mechanism together with users data and apply access policies with respect to users data. We use JAR programming which provides the dynamic and traveling object functionality and to track any access to userâs data will call authentication and automated logging mechanism to the JAR files. Each access to users cloud data will be getting recorded in separate log file. To provide robust users control, distributed auditing functionality is also provided to track the usage of data. The proposed system also provides the authentication mechanism using external channels and also makes a log of user details from which the cloud data is accessed. Only data owner can retrieve the detail log of his data as per requirement. Data owner will provide the type of access to his data and based on that, authorized data user can access the data over the cloud environment.